2000
DOI: 10.1098/rspb.2000.1175
|View full text |Cite
|
Sign up to set email alerts
|

Androgen levels and female social dominance inLemur catta

Abstract: Morphological and behavioural traits which improve agonistic power are subject to intrasexual selection and, at the proximate level, are in£uenced by circulating androgens. Because intrasexual selection in mammals is more intense among males, they typically dominate females. Female social dominance is therefore unexpected and, indeed, rare. Ring-tailed lemurs (Lemur catta) are sexually monomorphic primates in which all adult females dominate all males. The goal of our study was to test the prediction that fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 56 publications
5
59
1
Order By: Relevance
“…Our results for the relationship between fecal androgens and rank in female mandrills are similar to those reported for female yellow baboons (fecal testosterone, Altmann et al, 1995), ring-tailed lemurs (fecal and salivary testosterone, von Engelhardt et al, 2000), and bonobos (fecal 5a-androstan-17a-ol-3-one, Sannen et al, 2004), in which rank is also not related to androgens. However, our findings differ from those for captive talapoins (serum testosterone, Batty et al, 1986), hybrid baboons (fecal testosterone, Beehner et al, 2005), and Barbary macaques (fecal 17b-OH-androgens, Grant et al, 2011), in which dominant females show higher androgen levels than subordinates.…”
Section: Fecal Androgens Age and Dominance Ranksupporting
confidence: 76%
See 2 more Smart Citations
“…Our results for the relationship between fecal androgens and rank in female mandrills are similar to those reported for female yellow baboons (fecal testosterone, Altmann et al, 1995), ring-tailed lemurs (fecal and salivary testosterone, von Engelhardt et al, 2000), and bonobos (fecal 5a-androstan-17a-ol-3-one, Sannen et al, 2004), in which rank is also not related to androgens. However, our findings differ from those for captive talapoins (serum testosterone, Batty et al, 1986), hybrid baboons (fecal testosterone, Beehner et al, 2005), and Barbary macaques (fecal 17b-OH-androgens, Grant et al, 2011), in which dominant females show higher androgen levels than subordinates.…”
Section: Fecal Androgens Age and Dominance Ranksupporting
confidence: 76%
“…However, there is no relationship between rank and fecal testosterone in female yellow baboons (Papio cynocephalus, Altmann et al, 1995), between rank and fecal and salivary testosterone in ring-tailed lemurs (Lemur catta, von Engelhardt et al, 2000), or between rank and fecal 5a-androstan-17a-ol-3-one in bonobos (Pan paniscus, Sannen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies have involved analysis of salivary cortisol to assess adrenal activity in relation to behaviour and acute stress (e.g. Ange-van Heugten et al, 2009;Cross et al, 2004;Hohmann et al, 2009;Kuhar et al, 2005), although the measurement of reproductive hormones has also been reported (DiGiano et al, 1992;von Engelhardt et al, 2000). 6 M. Heistermann: Non-invasive monitoring of endocrine status in laboratory primates 2.4 Hormone analysis from hair Steroid hormones from blood are able to diffuse into the cells of the hair follicle and subsequently become deposited in the hair shaft from which they can be measured (Koren et al, 2002).…”
Section: Saliva Collection and Examples Of Applicationmentioning
confidence: 99%
“…Ange-van Heugten et al, 2009;Hohmann et al, 2009;Pearson et al, 2008;von Engelhardt et al, 2000). This procedure allows samples to be collected voluntarily from animals on a regular basis and under various housing conditions, including group-living.…”
Section: Saliva Collection and Examples Of Applicationmentioning
confidence: 99%